ELECTRONIC COMMUNICATION IN CIVIL LITIGATION - Salma, Marija (Zbornik radova Pravnog fakulteta u Novom Sadu, 2015)
This paper looks into common European and national rules regulating electronic communication in legal matters. Such form of communication in legal matters expedites the procedure. It is also pointed out that electronic communication between the court and the parties to the proceedings, as well as third parties, is conducted through registries, regulated by special regulations, for filing written submissions of the parties and decisions of the court. Legislation regulating electronic communication is intended for litigation in commercial matters. European and national rules do not exclude the possibility of electronic communication in non-commercial litigation provided there is an express consent of the parties to such communication. Although steps towards digitalization have been taken in the Republic of Serbia, legislation regulating electronic service of documents, communication in civil litigation, is still missing. The Civil Procedure Law does not have a separate section regulating the electronic communication in legal matters. However, it cannot be said that the CPC does not set basic principles regulating this form of communication in legal matters.